1979
DOI: 10.7326/0003-4819-90-2-243
|View full text |Cite
|
Sign up to set email alerts
|

Use of Laboratory Tests in a Teaching Hospital: Long-Term Trends

Abstract: We have assessed long-term trends in the use of laboratory tests among patients hospitalized on the medical service of a large teaching hospital. A significant decline in numbers of chemistry tests and no growth in numbers of microbiology or hematology tests or roentgenograms were noted between 1970 and 1977. Per-patient increases in laboratory costs and charges were considerably less than increases in total hospitalization costs and charges. These findings contrast to an average increase of 13.8% per year in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…Educational and administrative strategies in teaching hospitals can drastically reduce the use of subsidiary examination, with less discomfort for the patient, no impairment of care and with an important reduction of expenses 30,31 . Thurow reported that in The United States there is a great preoccupation with the growing expenses in health and thinks that this problem needs to be solved more in an ethical than in an economical way 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Educational and administrative strategies in teaching hospitals can drastically reduce the use of subsidiary examination, with less discomfort for the patient, no impairment of care and with an important reduction of expenses 30,31 . Thurow reported that in The United States there is a great preoccupation with the growing expenses in health and thinks that this problem needs to be solved more in an ethical than in an economical way 32 .…”
Section: Discussionmentioning
confidence: 99%
“…We limit our discussion here to physician-oriented interventions, recognizing that larger issues of reimbursement policies, efficiency of labo ratory services, and cost-effectiveness of laboratory tests also play major parts in the problems associated with low-cost diagnostic tests (3,37,45). Griner reported in 1979 the results of a sustained, multipronged effort to improve laboratory utilization in a teaching hospital (30). The median number of chemistry tests per hospitalized patient (counting an automated battery as a single test) fell from 18 in 1970 to 13 in 1977.…”
Section: Interventions To Improve Use Of Clinical Chemistriesmentioning
confidence: 99%
“…Many possible explanations for overuse of laboratory tests have been ad vanced (3,30). Among these are the following.…”
Section: Reasons Fo R Overusementioning
confidence: 99%
“…A multitude of factors contributing to excessive laboratory test utilization has been described in the literature (1,35,49 (11,64,72 (50). It has been noted that a "blanket requester" who orders unnecessary tests may reduce inpatient length of stay and costs compared with the "traditional selector," who reviews initial diagnostic test results before selecting additional studies (60).…”
Section: Increase In Laboratory Test Utilization Increasing Laboratormentioning
confidence: 99%
“…Expenses are accrued for activities other than the pursuit of new knowledge. Some university teaching centers emphasize complete patient workups, and the house officer must submit to teacher demands (35,39,49). Other residents believe that their peers or teachers will be impressed if all possible testing has been performed (39).…”
Section: Physician Education Role In Increased Laboratory Testingmentioning
confidence: 99%